Innovation of Story-Based Moral Learning Modules in Strengthening Student Character - Farhan Qomarudin; Ahmad Syarifuddin Zuhri (LP3M Pascasarjana STAI Ibnurusyd, 2025)
This study aims to develop and test the effectiveness of a story-based moral learning module as an innovation in strengthening students' character. The background of this study is based on the weak implementation of character education which tends to be normative and non-contextual. The story-based module is designed to touch the cognitive, affective, and psychomotor aspects of students through narratives that are relevant to their lives. The research method used is the Research and Development (R&D) model of Borg & Gall, with stages of needs analysis, planning, development, expert validation, revision, limited trials, and evaluation of effectiveness through a quasi-experimental approach. The results of the study showed that the use of story-based modules significantly improved students' understanding and internalization of moral values, such as honesty, responsibility, and empathy. This module is also able to build students' emotional involvement and create a fun and meaningful learning atmosphere. These findings strengthen the theory that the narrative approach can be an effective strategy in character learning. Thus, this module has great potential to be widely replicated in the context of character education at various school levels.